The Utilization of Printed and Online Dictionaries among Junior High School Students - Delona Ria Polhaupessy (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study explores the utilization of printed and online dictionaries by junior high school students in remote areas of Indonesia, focusing on their experiences, challenges and impacts on language acquisitions. In digital era, students access resources differently. The research highlights both the strengths and limitations of each dictionary type and concludes that internet-enabled dictionaries, for instance, are easy to use and have many features, while insufficient internet or devices are major concerns. However, the authors argue that while printed dictionaries are useful for definitions, they are often outdated and lack sufficient copies. The results indicate that teachers need to provide specific educational assistance to students, especially in the areas of digital literacy and skills of using the dictionaries. Such modification, which utilizes both printed and online dictionaries, would make an ideal learning experience in responding to the different learning preferences and requirements of students as well as enhancing language comprehension and skills in vocabulary and communication in this digital age.